The Effect of Unconventional Cytokine Combinations on NK-Cell Responses to Viral Infection - Ochayon, David E.; Waggoner, Stephen N. (Frontiers in Immunology, 2021)
Cytokines are soluble and membrane-bound factors that dictate immune responses. Dogmatically, cytokines are divided into families that promote type 1 cell-mediated immune responses (e.g., IL-12) or type 2 humoral responses (e.g., IL-4), each capable of antagonizing the opposing family of cytokines. The discovery of additional families of cytokines (e.g., IL-17) has added complexity to this model, but it was the realization that immune responses frequently comprise mixtures of different types of cytokines that dismantled this black-and-white paradigm. In some cases, one type of response may dominate these mixed milieus in disease pathogenesis and thereby present a clear therapeutic target. Alternatively, synergistic or blended cytokine responses may obfuscate the origins of disease and perplex clinical decision making. Most immune cells express receptors for many types of cytokines and can mediate a myriad of functions important for tolerance, immunity, tissue damage, and repair. In this review, we will describe the unconventional effects of a variety of cytokines on the activity of a prototypical type 1 effector, the natural killer (NK) cell, and discuss how this may impact the contributions of these cells to health and disease.